The fundamental niche of blood oxygen binding in the pelagic ocean. Issue 7 (22nd October 2015) - Mislan, K. A. S.; Dunne, John P.; Sarmiento, Jorge L.
Abstract : Marine species ranging in size from microscopic zooplankton to large predatory fish move vertically in the ocean water column to forage for food and avoid predators. Oxygen and temperature decrease, often rapidly, from shallow to deeper depths, restricting the ability of species to use the vertical habitat. One physiological trait that determines the tolerance of organisms to low oxygen is the oxygen affinity of oxygen carrier proteins, hemoglobin and hemocyanin, in the blood. To quantify the range of oxygen affinities for marine organisms, we surveyed the literature for measurements of oxygen binding to blood at multiple temperatures to account for its temperature sensitivity. Oxygen affinity is mapped within the ocean environment using the depth at which oxygen pressure decreases to the point at which the blood is 50% oxygenated (P50 depth) as organisms move from the surface to depth in the ocean water column. We find that vertical gradients in both temperature and oxygen impact the vertical position and areal extent of P50 depths. Shifts in P50 due to temperature cause physiological types with the same P50 in the surface ocean to have different P50 depths and physiological types with different P50 's in the surface ocean to have the same P50 depth. The vertical distances between P50 depths are spatially variable, which may determine the frequency of ecological interactions, such as competition and predation. In summary, P50 depth, which represents a key physiological transition point between dexoxygenated and oxygenated blood, provides mechanistic insight into organism function within the water column of the global ocean.